Magnetically frustrated double perovskites: Synthesis, structural properties, and magnetic order of Sr2BOsO6 (B = Y, In, Sc) - Paul, Avijit Kumar; Sarapulova, Angelina; Adler, Peter; Reehuis, Manfred; Kanungo, Sudipta; Mikhailova, Dana; Schnelle, Walter; Hu, Zhiwei; Kuo, Changyang; Siruguri, Vasudeva; Rayaprol, Sudhindra; Soo, Yunlian; et al. (Zeitschrift für Anorganische und Allgemeine Chemie, 2015)
Double perovskites Sr2BOsO6 (B = Y, In, and Sc) were prepared from the respective binary metal oxides, and their structural, magnetic, and electronic properties were investigated. At room temperature all these compounds crystallize in the monoclinic space group P21/n. They contain magnetic osmium (Os5+, t2g3) ions and are antiferromagnetic insulators with Néel temperatures TN = 53 K, 26 K, and 92 K for B = Y, In, and Sc, respectively. Powder neutron diffraction studies on Sr2YOsO6 and Sr2InOsO6 showed that the crystal structures remain unchanged down to 3 K. The Y and In compounds feature a type I antiferromagnetic spin structure with ordered Os moments of 1.91 μB and 1.77 μB, respectively. The trend in TN does not simply follow the development of the lattice parameters, which suggests that d0 compared to d10 ions on the B site favor a somewhat different balance of exchange interactions in the frustrated Os5+ fcc-like lattice.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Antiferromagnetism; Double perovskite oxides; Magnetic frustration; Neutron diffraction